Uova fatali. I: Il sistema scenico-drammatico neosovietico russo negli anni della formazione (1924-1928) - Lenzi, Massimo (Mimesis Journal, 2020)
This text is the first part of a broader investigation aimed at reconstructing typologies, institutions and structures of the Russian-speaking theatre-drama production system in the early years of the Soviet State (1924-1928), as well as the activity of its main protagonists. In particular, moving from an historiographical Brief premise, this text examines the passage from the spectacular typologies peculiar to the years of the civil war (agitki, massovki, etc.) to the context in which the new genre of heroic-revolutionary drama arose; the interactions between this and some of the thematic and structural characteristics of contemporary films production; the institutionalization of the scenic-dramatic collectives which were already operating in the revolutionary field (self-active theaters, Proletkul't); and the more or less conflictual relations between the Art Theatre and its main Studios.